Prediction of Reperfusion and Infarct Related Artery Patency after Thrombolysis in Acute Anterior Myocardial Infarction by Degree of P Wave Dispersion on ECG - Khan, Md Monir Hossain; Rahman, Md Afzalur; Majumder, Abdullah Al Shafi; Hussain, Khondker Shaheed; Rahman, Md Toufiqur; Haque, Md Monsurul; Ullah, Mohammad; Siddiqui, Mohammad Khalilur Rahman; Islam, Md Sariful; Rahman, Md Azijur (Cardiovascular Journal, 2018)
Background: Early detection IRA patency following thrombolytic therapy is of great importance in terms of prognosis and identification of candidates for rescue percutaneous coronary intervention (PCI). P wave dispersion (PWD), a new parameter measured before and after thrombolytic therapy is supposed to predict successful reperfusion in patients with anterior acute myocardial infarction (AMI). Methods: 132 patients were selected and divided into two groups on the basis of ST Segment resolution (STR) after 120 minutes of thrombolysis. Group I: patients with STR >70%; Group II: patients with STR < 70%. P wave dispersion was measured in both groups before and after thrombolysis. All patients underwent coronary angiography (CAG). IRA was considered patent if TIMI flow grade was e”2. Results: It was observed that diabetes mellitus and dyslipidemia were significantly higher in group II patients (p=0.04 and p=0.03, respectively). PWD before thrombolysis (PWD0) and 90 minutes after thrombolysis (PWD90) in both groups were statistically insignificant (p=0.45 and p=0.19, respectively). The mean level of PWD120 was statistically significant (p=0.001). After multivariate regression analysis PWD120 was found to be the significant predictor of IRA patency (OR = 1.101; 95% CI = 1.012 – 1.240; p = 0.01). Conclusion: P wave dispersion in patients receiving thrombolytic therapy can be a predictor of successful reperfusion and patent IRA. PWD values, in combination with other reperfusion parameters, can contribute to the identification of rescue PCI candidates. Cardiovasc. j. 2018; 10(2): 158-163